The Path towards a Unified Health System in India: From Fragmentation to Integration: A Narrative Review - Shubham Bobade; Sheetal Asutkar (Journal of Clinical and Diagnostic Research)
India’s healthcare system is a complex structure divided into public and private sectors. The public sector, funded and managed by the government, aims to offer accessible and affordable healthcare to the citizens. It includes a network of primary health centres, district hospitals, and specialised medical institutions like the All India Institute of Medical Sciences (AIIMS). In contrast, the private sector, comprising of the small clinics and large hospitals offering a wide range of services often at a higher cost. This dual structure reflects the challenges of ensuring equitable access to quality healthcare across the country, highlighting the need for integrated strategies to bridge the gap between these sectors. This review discusses a patient-centric model, rather than a pathy-centric one, which can offer a more effective healthcare solution. Patient-centric models offer various health services at a single point of contact, allowing patients to benefit from the strengths of different systems of medicine in one place. Achieving this model requires a multilevel approach, with systems of medicine functioning alongside each other as complementary services. Key areas for integration include clinical practice, medical education, and research, all aimed at fostering a patient-centric approach. The benefits of such an integrated system include holistic health approaches, improved accessibility, and enhanced research opportunities. However, significant hurdles must be addressed, including cultural biases, regulatory fragmentation, and the need for evidence-based practices. Strategies for overcoming these challenges include the development of supportive national health policies, educational reforms, and community engagement initiatives. This review article explores the concept of “One Nation, One Health System”, which proposes the integration of traditional and modern health practices into a unified framework to enhance healthcare delivery.